Influence of Global Climate Changes on Cereal Crops Yield in Rainfall Lands in Uzbekistan - Mamatkul Abdurahmanovich Juraev; Abdugafurjon Abdivakhabovich Holdorov. (Zien Journals, 2023)
The consequences of the global warming of the world's climate are felt in the rainfed regions of the republic. Climate change will have a negative impact on the food security of the population living in dry regions. As a result of global warming, the frequency of droughts has accelerated, until 2010, severe droughts occurred every 8-10 years. In recent years, it has been observed that during the period of grain filling and ripening of grain crops, drought occurs along with strong anomalous heat.
Keywords: bread wheat; barley; rainfed lands; rainfall